Controlled growth of dense and ordered metal–organic framework nanoparticles on graphene oxide1. Issue 18 (4th March 2015) - Qiu, Xuan; Wang, Xi; Li, Yingwei
<x xml:space="preserve">Abstract</x> A facile synthetic strategy is developed to modulate the growth and distribution of MOF–graphene oxide (GO) nanohybrids, achieving dense and ordered MOFs featuring different sizes and morphologies dispersed on GO.